Aeropuerto regional de carga Santiago Vila (2021)
Energy consumption is one of the factors that most contributes to deterioration environment of the planet, however, seen from the architecture there are sources of consumption predominant energy sources, one of these foci are airports. Taking this in account seeks to design an airport that meets all the characteristics of a sustainable building without neglecting each and every one of the requirements technical and normative for the correct operation of these. Based on how they go The SDG in Colombia seeks to consolidate the aeronautical project in an area that be of great contribution to the specific region and that has the physical conditions and techniques for planning the airport, Santiago Vila Airport is chosen, as starting point for the use and reuse of the infrastructure on the air, thus greatly reducing materials and construction works by making use of this.